Validation of a liquid chromatography/tandem mass spectrometry method for the detection of aflatoxin B1 residues in broiler liver - Magnoli, Alejandra Paola (2018)
Aflatoxin B1 is a carcinogenic and mutagenic mycotoxin produced mainly by Aspergillus flavus and Aspergillus parasiticus. It is the predominant mycotoxin found in raw materials used for the manufacture of broiler feeds. The aim of the present study was to develop a new and optimized method for the detection and quantification of aflatoxin B1 (AFB1) residues in broiler liver using solid phase extraction (SPE) clean-up and liquid chromatography-electrospray ionization/tandem mass spectrometry (LC–ESI-MS/MS) detection. The method was validated for linearity, accuracy, precision, limit of detection (LOD) and limit of quantification (LOQ). The validation parameters indicated satisfactory linearity (r2 > 0.99), accuracy and precision (4.57% intra-day RSD; 14.65% inter-day RSD) a very high recovery (99 ± 13%) and high sensitivity achieved for AFB1 in animal samples (LOD = 0.017 and LOQ = 0.050 ng/g). The method was effective for the detection and quantification of AFB1 residues in broiler liver and could also be potentially used for detecting AFB1 in other edible animal tissues after natural or experimental AFB1 exposure with high sensitivity and precision.